Modeling Lymphoma Angiogenesis, Lymphangiogenesis, and Vessel Co-Option, and the Effects of Inhibition of Lymphoma–Vessel Interactions with an αCD20-EndoP125A Antibody Fusion Protein - Christian Elledge; Yu Zhang; Seung-Uon Shin; Hyun-Mi Cho; Sundaram Ramakrishnan; Ankita Sankar; Jennifer R. Chapman; Daniel Bilbao; Rathin Das; Hava Gil-Henn; Izidore S. Lossos; Joseph D. Rosenblatt (Cells)
Lymphoma growth, progression, and dissemination require tumor cell interaction with supporting vessels and are facilitated through tumor-promoted angiogenesis, lymphangiogenesis, and/or lymphoma vessel co-option. Vessel co-option has been shown to be responsible for tumor initiation, metastasis, and resistance to anti-angiogenic treatment but is largely uncharacterized in the setting of lymphoma. We developed an in vitro model to study lymphoma–vessel interactions and found that mantle cell lymphoma (MCL) cells co-cultured on Matrigel with human umbilical vein (HUVEC) or human lymphatic (HLEC) endothelial cells migrate to and anneal with newly formed capillary-like (CLS) or lymphatic-like (LLS) structures, consistent with lymphoma–vessel co-option. To inhibit this interaction, we constructed an antibody fusion protein, αCD20-EndoP125A, linking mutant anti-angiogenic endostatin (EndoP125A) to an αCD20-IgG1-targeting antibody. αCD20-EndoP125A inhibited both CLS and LLS formation, as well as MCL migration and vessel co-option. Lymphoma vessel co-option requires cell migration, which is regulated by chemokine–chemokine receptor interactions. CXCL12 and its receptor, CXCR4, are highly expressed by both endothelial cells forming CLS and by MCL cells during vessel co-option. αCD20-EndoP125A suppressed expression of both CXCL12 and CXCR4, which were required to facilitate CLS assembly and vessel co-option. We also tested αCD20-EndoP125A effects in vivo using an aggressive murine B cell lymphoma model, 38c13-hCD20, which demonstrated rapid growth and dissemination to tumor-draining lymph nodes (TDLNs) and the spleen, lung, and brain. The pattern of lymphoma distribution and growth within the lung was consistent with vessel co-option. As predicted by our in vitro model, αCD20-EndoP125A treatment inhibited primary tumor growth, angiogenesis, and lymphangiogenesis, and markedly reduced the number of circulating tumor cells and lymphoma dissemination to TDLNs and the lungs, spleen, and brain. αCD20-EndoP125A inhibited lymphoma vessel co-option within the lung. Marked inhibition of MCL primary tumor growth and dissemination were also seen using an MCL xenograft model. The ability of αCD20-EndoP125A to inhibit angiogenesis, lymphangiogenesis, and lymphoma vessel co-option provides a novel therapeutic approach for inhibition of lymphoma progression and dissemination.